IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN IPS KELAS VIII C SMPN 04 SUNGAI RAYA KABUPATEN KUBU RAYA - Iwan Saputra; Sulistyarini Sulistyarini; Agus Sastrawan Noor (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research was a qualitative research with a descriptive method. The subject of this research was social studies learning teachers and students of SMPN 04 Sungai Raya. Data collection techniques used in this research were observations, interviews, and documentation. The results of this study were in the planning process was prepared before learning began and it was seen that in the lesson plan (RPP) the teacher wanted to carry out character education in the classroom. While implementation of social studies learning has been the teacher implementing character education in social studies learning in class VIII C and in accordance with the lesson plans. Where character education was listed in Permindibud Regulation No. 20 of 2018 article 2 paragraph 2. Evaluation carried out by teachers in social studies learning regularly. The obstacles in implementing character education, were the lack of awareness of students to obey the rules, lack of motivations to learn, lack of responsibility, limited facilities and infrastructure. Keywords: Character Education, Implementation, Social Studies Learning